2001
DOI: 10.1016/s0344-0338(04)70171-5
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Supernumerary OvaryOne with Large Fibroma with Meig's Syndrome and the Other with Endometriosis and Cystic Change

Abstract: Reports of supernumerary ovaries are rare. We describe two such cases, one with fibroma and the other with endometriosis and cystic change. A large fibroma measuring 17.4 x 12.0 x 7.5 cm in size was found in the supernumerary ovary of the omentum in the first case of a 47-year-old married woman with Meig's syndrome. The second case was associated with endometriosis and cystic change, measuring 11 x 5 x 3 cm in size and located in the upper abdominal cavity. It was attached to the uterus of a 28-year-old pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…there have been only a few reports of tumors arising in accessory ovaries; examples of these are cystic mature teratomas, 1 serous cystadenomas, 4 mucinous cystadenomas, Brenner tumor, 5 ste roid cell tumor, 6,7 and sclerosing stromal tumor 2 ( Table 1). A case of a large fibroma arising in supernumerary ovary has been reported, 8 to our knowledge, the occurrence of a fibroma in an accessory ovary has not yet been reported. A fibroma is a common ovarian tumor, occurring almost in variably after puberty and histologically characterized by closely packed spindle stromal cells arranged in a "feather stitched" or storiform pattern.…”
Section: Discussionmentioning
confidence: 83%
“…there have been only a few reports of tumors arising in accessory ovaries; examples of these are cystic mature teratomas, 1 serous cystadenomas, 4 mucinous cystadenomas, Brenner tumor, 5 ste roid cell tumor, 6,7 and sclerosing stromal tumor 2 ( Table 1). A case of a large fibroma arising in supernumerary ovary has been reported, 8 to our knowledge, the occurrence of a fibroma in an accessory ovary has not yet been reported. A fibroma is a common ovarian tumor, occurring almost in variably after puberty and histologically characterized by closely packed spindle stromal cells arranged in a "feather stitched" or storiform pattern.…”
Section: Discussionmentioning
confidence: 83%
“…Fei et al 8 reported a case of accessory ovary cyst complicated with torsion, presented with acute lower abdominal pain, nausea and vomiting, simultaneously with low fever and leukocytosis, these symptoms and signs were similar with cyst torsion in the orthotopic ovary. In addition, Kamiyama et al 17 reported torsion of a supernumerary ovarian endometrial cyst in a 28-year-old pregnant woman (40 weeks gestation). The cyst that attached to the pregnant uterus was removed surgically, and postoperative pathology confirmed hemorrhage and necrosis within the cyst wall, which was pathologically consistent with torsion of ovarian endometrial cyst.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The literature reports various cases of tumors arising in ectopic ovaries, such as serous cystadenoma, dermoid cyst, Brenner tumor, sclerosing stromal tumor, steroid cell tumor, mucinous cystadenoma, teratoma and fibroma. 6,[14][15][16][17][18][19] Since 1864 there have been less than 50 cases of ectopic ovary reported in the literature and only in two cases the diagnosis was established prior to the operation. 6,14 Despite the strong association with pathological processes, supernumerary and accessory ovarian tissue has been notoriously difficult to diagnose preoperatively.…”
Section: Discussionmentioning
confidence: 99%